2015
DOI: 10.1371/journal.pone.0120162
|View full text |Cite
|
Sign up to set email alerts
|

Lewisy Promotes Migration of Oral Cancer Cells by Glycosylation of Epidermal Growth Factor Receptor

Abstract: Aberrant glycosylation changes normal cellular functions and represents a specific hallmark of cancer. Lewisy (Ley) carbohydrate upregulation has been reported in a variety of cancers, including oral squamous cell carcinoma (OSCC). A high level of Ley expression is related to poor prognosis of patients with oral cancer. However, it is unclear how Ley mediates oral cancer progression. In this study, the role of Ley in OSCC was explored. Our data showed that Ley was upregulated in HSC-3 and OC-2 OSCC cell lines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
0
18
2
Order By: Relevance
“…EGFR is a scaffold carrying α1,3-fucosylation, particularly the LeY epitope. 34 Based on the above results showing that FUT4 is a potential target for miR-200b that may regulate its expression, we hypothesized that miR-200b altered LeY synthesis and EGFR activation. The results of a blotting analysis showed that miR-200b mimics transfection induced a decreased expression of α1,3-fucosylation of glycoproteins by Lotus Tetragonolobus Lectin (LTL) (which specifically recognizes and binds to α1,3-fucosylated glycans) blotting analysis ( Figures 6a and b ), whereas Anti-miR-200b facilitated cell surface α1,3-fucosylation synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EGFR is a scaffold carrying α1,3-fucosylation, particularly the LeY epitope. 34 Based on the above results showing that FUT4 is a potential target for miR-200b that may regulate its expression, we hypothesized that miR-200b altered LeY synthesis and EGFR activation. The results of a blotting analysis showed that miR-200b mimics transfection induced a decreased expression of α1,3-fucosylation of glycoproteins by Lotus Tetragonolobus Lectin (LTL) (which specifically recognizes and binds to α1,3-fucosylated glycans) blotting analysis ( Figures 6a and b ), whereas Anti-miR-200b facilitated cell surface α1,3-fucosylation synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…After confirmation of the whole α1,3-fucosylation alteration by miR-200b transfection, we further selected LeY as a representative of α1,3-fucosylated glycans to analyze the effect of miR-200b. LeY, which contains an α1,3-fucosylation epitope is carried by many glycoproteins, including EGFR, 34 CD44 51 and MUC6, 52 on the cancer cells’ surface. EGFR is closely correlated with cancer cells’ proliferation and metastasis via the activation of EGFR and downstream signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…36 Increased expression of Lewis y promotes cell proliferation and migration through activation of EGFR signal pathway. 15,50,51 Accordingly, there is a good possibility that Lewis y regulates the expression of CD44 via BCL6 by activation of EGFR signal to enhance the malignant behaviors in ovarian cancer, whereas the mechanisms are still warranted more in-depth and concentrated investigations.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR stimulation induces cell migration through the activation of matrix metalloproteinases (MMPs) (24), signal transducer and activator of transcription 3 (STAT3) (25,26) or the MEK/ERK and PI3K signaling pathways (9), and may be associated with an epithelial-mesenchymal transition (EMT)-like phenotype (27). Furthermore, cross-talk between EGFR and G-protein-coupled receptors contributes to cell migration (28,29).…”
Section: Introductionmentioning
confidence: 99%